Menstrual cycle resumption and female fertility after autologous hematopoietic stem cell transplantation for multiple sclerosis. (November 2021) - Massarotti, Claudia; Sbragia, Elvira; Boffa, Giacomo; Vercelli, Caterina; Zimatore, Giovanni Bosco; Cottone, Salvatore; Frau, Jessica; Raiola, Annamaria; Varaldo, Riccardo; Mancardi, Gianluigi; Inglese, Matilde; Anserini, Paola
Data on fertility after autologous hematopoietic stem cell transplantation (aHSCT) in women with multiple sclerosis (MS) are inconclusive. This study aims to report on post-aHSCT menstrual resumption in a multi-center MS-women cohort. Out of 43 women, 30 (70%) recovered menses after a mean time of 6.8 months. Older age (odds ratio (OR) = 0.5, p < 0.0001) and previous pulsed cyclophosphamide (OR = 0.44, p = 0.005) were independently associated with a reduced menstrual recovery probability. Conditioning regimens' intensity resulted not associated with post-procedure amenorrhea. Our results highlight younger age as significantly associated with menses recovery; proper fertility counseling for MS women candidated to aHSCT both prior- and post-transplantation is therefore warranted.